Alectinib following brigatinib: an efficient sequence for the treatment of advanced anaplastic lymphoma kinase-positive lung cancer patients. Issue 1 (January 2021) - Hochmair, Maximilian Johannes; Prosch, Helmut; Krenbek, Dagmar; Weinlinger, Christoph; Fabikan, Hannah; Valipour, Arschang
Abstract : Anaplastic lymphoma kinase (ALK)-translocations are present in up to 5% of non-small cell lung cancer (NSCLC), most of them being adenocarcinomas. Even though the availability of five potent ALK-inhibitors for the treatment of ALK-positive NSCLC patients, there is no consensus about the ideal therapy sequence. Alectinib has been so far successfully and routinely used as first-line therapy, especially in patients presenting central nervous system lesions; however, with the very recent European approval of brigatinib in the first line, a new treatment option is now available for ALK+ patient collective. In this case series, efficient systemic and intracranial responses to alectinib late-line treatment following brigatinib therapy are reported. This therapeutic sequence is going to gain therefore more importance in a near future